ANALISIS SALURAN PEMASARAN LADA PUTIH DI DESA AIR GEGAS KECAMATAN AIR GEGAS KABUPATEN BANGKA SELATAN: Analysis of Marketing Channels for White Pepper in Air Gegas Village, Air Gegas District, South Bangka Regency - Atmaja, Eddy Jajang; Udayana, Made Andhika; Purwasih, Rati (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2024)
This research aims to: (1) determine pepper marketing channels (2) calculate pepper marketing margin (3) calculate pepper farmer share (4) analyze pepper marketing efficiency in Air Gegas Village. The research method used in this research is the survey method. The sampling technique used snowball sampling and the number of samples was 10 farmers and 2 trader collectors. The data collection methods used were interviews, observation and questionnaires. The data analysis method uses qualitative analysis, marketing margin analysis, farmer share analysis and marketing efficiency analysis. The research results show that 1) the marketing channels for pepper in Air Gegas Village are indirect selling and collecting traders as intermediaries. 2). The average marketing margin for pepper in Air Gegas Village is Rp. 4,500/kg. 3). The average farmer share of pepper in Air Gegas Village is 96.4%. 4). The average pepper marketing efficiency in Air Gegas Village is 1.83%.